ANTIMALARIAL ACTIVITY OF CRUDE EXTRACTS OF ARTOCARPUS HETEROPHYLLUS, ARTOCARPUS ALTILIS, AND ARTOCARPUS CAMANSI - Hafid, Achmad Fuad; Febrianty, Niniet; Septiani, Ria Putri; Ranggaditya, Dimas; Fabriana, Lintang Hudha; Widyawaruyanti, Aty (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: This research investigated in vitro and in vivo antimalarial activity of leaves and stem bark crude extract of Artocarpus species, focusing on Artocarpus heterophyllus, Artocarpus altilis, and Artocarpus camansi against Plasmodium falciparum and Plasmodium berghei. Methods: Leaves and stem bark extracts of three Artocarpus species were tested for their antimalarial activities. The antimalarial in vitro test was conducted using P. falciparum (3D7 strain) culture in RPMI-1640 medium, while the antimalarial in vivo test was performed based on Peter's test (The 4 days suppressive test) that using P. berghei (strain ANKA) infected mice. Results: From total 6 extracts of Artocarpus leaves and stembark, 2 extracts showed good antimalarial activities against P. falciparum and P. berghei. A. heterophyllus leaves extract (AHL) and A. altilis leaves extract (AAL) were classified as good to moderately active against P. falciparum with inhibition concentration (IC ) value of 9.35 µg/ml and 1.32 µg/ml, respectively. In vivo antimalarial activity showed that AHL and AAL were very active against P. berghei with effective dose (ED 50 50 ) value of 8.33 mg/kg body weight and 0.82 mg/kg body weight, respectively. Conclusion: AAL has shown as the most active antimalarial activity with IC 50 value of 1.32 µg/ml and ED value of 0.82 mg/kg body weight. AAL may become a potential candidate of the antimalarial drug from Artocarpus species. Keywords: Artocarpus heterophyllus, Artocarpus altilis, Artocarpus camansi, Antimalarial activity. 50